PiMan: System Manager of the "Pi of the Sky" Experiment. (26th January 2010) - Nawrocki, Krzysztof; Ptasińska, Maria; Sokołowski, Marcin; Użycki, Janusz; Zaremba, Marcin
Abstract : This paper describes PiMan, a CORBA-based system manager of the "Pi of the Sky" experiment, whose prototype consisting of two cameras on parallactic mount is running at Las Campanas Observatory in Chile. We discuss in detail all software components of the "Pi of the Sky" system, interactions between them, and the architecture of the PiMan system. PiMan extension and other system software that will control and monitor final system being under construction, consisting of two sites with 16 CCD cameras installed on three mounts per site, is also described in this paper.